2019
DOI: 10.3390/app9214621
|View full text |Cite
|
Sign up to set email alerts
|

Vectored-Bloom Filter for IP Address Lookup: Algorithm and Hardware Architectures

Abstract: The Internet Protocol (IP) address lookup is one of the most challenging tasks for Internet routers, since it requires to perform packet forwarding at wire-speed for tens of millions of incomming packets per second. Efficient IP address lookup algorithms have been widely studied to satisfy this requirement. Among them, Bloom filter-based approach is attractive in providing high performance. This paper proposes a high-speed and flexible architecture based on a vectored-Bloom filter (VBF), which is a space-effic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 33 publications
0
7
0
Order By: Relevance
“…A functional Bloom filter (FBF) can return a value corresponding to an input as well as membership information regarding whether the input is an element of a set [35], [37]. The FBF has been used as a key-value structure in various network applications owing to its space-efficient characteristics [19], [34], [38]- [40]. The FBF utilizes the fact that various combinations of hash indexes of each key can be used to distinguish one key from other keys.…”
Section: B Functional Bloom Filtermentioning
confidence: 99%
“…A functional Bloom filter (FBF) can return a value corresponding to an input as well as membership information regarding whether the input is an element of a set [35], [37]. The FBF has been used as a key-value structure in various network applications owing to its space-efficient characteristics [19], [34], [38]- [40]. The FBF utilizes the fact that various combinations of hash indexes of each key can be used to distinguish one key from other keys.…”
Section: B Functional Bloom Filtermentioning
confidence: 99%
“…A functional Bloom filter (FBF) [20][21][22] is a variant of a standard Bloom filter that returns a value corresponding to a key as well as its membership. Figure 1d shows a functional Bloom filter with m cells and k hash indexes.…”
Section: Functional Bloom Filtermentioning
confidence: 99%
“…It is shown that the theoretical and simulation results become similar as the load factor increases. For the theoretical results of hash tables, Labels ( 16), (21), and (25) are used for α ≤ 1, and Labels (18), (23), and ( 27) are used for α > 1. In cases of the multi-hash table and the cuckoo hash table, parameters determining the performance of a data structure, such as the number of buckets and the number of hash functions, are the same, and therefore these tables have almost the same theoretical upper bounds.…”
Section: Performance Evaluationmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the process of finding an LMP is very complex and consumes a lot of cycles. Therefore, many researchers have been working on high-performance IP address lookup [1][2][3][4][5][6][7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%